How Do Individual Investors Trade? - Ingmar Nolte; Sandra Nolte (Verein für Socialpolitik, 2010)
This paper examines how high-frequency trading decisions of individual investors are influenced by past price changes. Specifically, we address the question as to whether decisions to open or close a position are different when investors already hold a position compared to when they don't. Based on a unique dataset from an electronic foreign exchange trading platform, OANDA FXTrade, we find that investors' future order flow is (significantly) driven by past price movements and that these predictive patterns last up to several hours. This observation clearly shows that for high-frequency trading, investors rely on previous price movements in making future investment decisions. We provide clear evidence that market and limit orders flows are much more predictable if those orders are submitted to close an existing position than if they are used to open one. We interpret this finding as evidence for the existence of a monitoring effect, which has implications for theoretical market microstructure models and behavioral finance phenomena, such as the endowment effect.
Keywords: G10; F31; C32; 330; Trading Activity Dataset; Order Flow; Foreign Exchange Market; Monitoring Effect